Project management support systems in the SaaS model in the activity of virtual organizations - Dziembek, Damian (Systemy wspomagania zarządzania projektem w modelu SaaS w działalności organizacji wirtualnych, 2020)
Nowadays, the Software as a Service model is an increasingly popular method of acquiring and using IT systems such as project management support systems. The SaaS model consists in making IT systems available in the Internet space for a fee, which users can use online. The aim of the article is to analyse the possibilities of using project management support systems offered in the SaaS model in the activities of a virtual organization. The article introduces virtual organizations, emphasizing their features, structure and the role of IT technology in their functioning. The next section presents the general characteristics of the SaaS model and highlights the benefits and risks of using PMS systems in the SaaS model. Then, various conditions related to the purchase and use of PMS systems were signalled in the form of a service supporting the activities of a virtual organization. Finally, some PMS systems available in the SaaS model that can support the activities of domestic and international virtual organizations were listed
Informatyka Ekonomiczna = Business Informatics, 2020, Nr 4 (58), s. 93-110
Keywords: informatyka ekonomiczna